Preoperative Association Between Quantitative Lumbar Muscle Parameters and Spinal Sagittal Alignment in Lumbar Fusion Patients. Issue 23 (1st December 2022) - Moser, Manuel; Okano, Ichiro; Albertini Sanchez, Leonardo; Salzmann, Stephan N.; Carlson, Brandon B.; Adl Amini, Dominik; Oezel, Lisa; Chiapparelli, Erika; Tan, Ek T.; Shue, Jennifer; Sama, Andrew A.; Cammisa, Frank P.; et al.
Abstract : Study Design: A retrospective cross-sectional study. Objective: To assess the association between spinal muscle morphology and spinopelvic parameters in lumbar fusion patients, with a special emphasis on lumbar lordosis (LL). Summary of Background Data: Maintenance of sagittal alignment relies on muscle forces, but the basic association between spinal muscles and spinopelvic parameters is poorly understood. Materials and Methods: Patients operated between 2014 and 2017 who had both lumbar magnetic resonance imaging scan and standing whole-spine radiographs within six months before surgery were included. Muscle measurements were conducted on axial T2-weighted magnetic resonance images at the superior endplate L3–L5 for the psoas and L3–S1 for combined multifidus and erector spinae (paraspinal) muscles. A pixel intensity threshold method was used to calculate the total cross-sectional area (TCSA) and the functional cross-sectional area (FCSA). Spinopelvic parameters were measured on lateral standing whole-spine radiographs and included LL, pelvic incidence (PI), PI-LL mismatch, pelvic tilt, sacral slope, thoracic kyphosis, and sagittal vertical axis. Analyses were stratified by biological sex. Multivariable linear regression analyses with adjustments for age and body mass index (BMI) were performed. Results: A total of 104 patients (62.5% female) were included in the analysis. The patient population was 90.4% White with a median age at surgery of 69 years and a median BMI of 27.8 kg/m 2 . All muscle measurements were significantly smaller in women. PI, pelvic tilt, and thoracic kyphosis were significantly greater in women. PI-LL mismatch was 6.1° (10.6°) in men and 10.2° (13.5°) in women ( P =0.106), and sagittal vertical axis was 45.3 (40.8) mm in men and 35.7 (40.8) mm in women ( P =0.251). After adjusting for age and BMI, paraspinal TCSA at L3–L5, and paraspinal FCSA at L4 showed significant positive associations with LL in women. In men, psoas TCSA at L5 and psoas FCSA at L5 showed significant negative associations with LL, but none of the paraspinal muscle measurements. Conclusion: Our findings indicate that psoas and lumbar spine extensor muscles interact differently on LL among men and women, creating a unique mechanical environment. Level of Evidence: Level 4.